Ethanol, not detectably metabolized in brain, significantly reduces brain metabolism, probably via action at specific GABA(A) receptors and has measureable metabolic effects at very low concentrations. (18th December 2013) - Rae, Caroline D.; Davidson, Joanne E.; Maher, Anthony D.; Rowlands, Benjamin D.; Kashem, Mohammed A.; Nasrallah, Fatima A.; Rallapalli, Sundari K.; Cook, James M.; Balcar, Vladimir J.
Abstract Ethanol is a known neuromodulatory agent with reported actions at a range of neurotransmitter receptors. Here, we measured the effect of alcohol on metabolism of [3‐13C]pyruvate in the adult Guinea pig brain cortical tissue slice and compared the outcomes to those from a library of ligands active in the GABAergic system as well as studying the metabolic fate of [1, 2‐13C]ethanol. Analyses of metabolic profile clusters suggest that the significant reductions in metabolism induced by ethanol (10, 30 and 60 mM) are via action at neurotransmitter receptors, particularly α4β3δ receptors, whereas very low concentrations of ethanol may produce metabolic responses owing to release of GABA via GABA transporter 1 (GAT1) and the subsequent interaction of this GABA with local α5‐ or α1‐containing GABA(A)R. There was no measureable metabolism of [1, 2‐13C]ethanol with no significant incorporation of 13C from [1, 2‐13C]ethanol into any measured metabolite above natural abundance, although there were measurable effects on total metabolite sizes similar to those seen with unlabelled ethanol. <boxed-text content-type="graphic" id="jnc12634-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Ethanol has many documented effects on brain neurochemistry including significantly decreasing glucose consumption. Here, we used multinuclear NMR spectroscopy and metabolomic neuropharmacology to examine alcohol effects on metabolism in cortical brain tissue slices. [1, 2‐13C]Ethanol is not metabolized by brain, but very low ethanol [0.1 mM] has significant effects on brain metabolism. Higher ethanol [1.0–60 mM] likely decreases metabolism through action at α4β3δ‐containing GABA(A) receptors.